Effects of Immunocastration and Amino Acid Supplementation on Yearling Fallow Deer (Dama dama) Testes Development - Chitambala, Thoniso; Ny, Veit; Ceacero, Francisco; Bartoň, Luděk; Bureš, Daniel; Kotrba, Radim; Needham, Tersia (Animals, 2023)
Forty-four fallow deer bucks (10 months old; 22.9 ± 2.4 kg) were utilized to investigate the effects of immunocastration and amino acid supplementation on testes development. Immunocastrated bucks were administered Improvac® at weeks 1, 8, and 20 of this study (control group: intact males). Starting at week 8, half of each sex received rumen-protected lysine and methionine (3:1) supplementation. At slaughter (week 37/39), body size, internal fat deposits, antler size parameters, testes weight, testes surface color, cauda epididymal sperm viability and morphology, and seminiferous tubule circumference and epithelium thickness were determined. Animals with larger body sizes, greater forequarter development, and antler growth also had greater testes development. Whilst the result of immunocastration on testes size is unexpected, testes tissue showed impaired development (atrophied seminiferous tubules), decreased sperm viability, and normal morphology. Testes tissue from immunocastrated deer was less red, possibly indicating reduced blood supply. Conversely, amino acid supplementation increased testes' redness and sperm viability, and intact males fed amino acids showed the greatest seminiferous tubule development. Thus, immunocastration may be a welfare-friendly alternative for venison production. Whilst the results support findings from the literature that testes size is not a reliable indicator of immunocastration success, this warrants further investigation in deer over different physiological development stages.
Keywords: welfare; sperm; venison; nutrition; castration; cervid